The leader's guide to coaching and mentoring : how to use soft skills to get hard results - Brent, Mike; Dent, Fiona Elsa (Pearson Education, 2015)
Coaching & mentoring skills are essential to help people reach their full potential. Once the preserve of qualified external coaches, all managers are now expected to apply these skills to get the most from their people. This guide provides the tools needed to coach & mentor within your role & unlock top performance in your people.